Synthesis and Monoamine Oxidase Inhibitory Activities of some 3-(4-Fluorophenyl)-5-aryl-N-substituted-4,5-dihydro-(1H)-pyrazole-1-carbothioamide Derivatives - Koç, G. Ş.; Tan, O. U.; Uçar, G.; Yıldırım, E.; Erol, K.; Palaska, E. (Drug Research, 2014)
28 new 3-(4-fluorophenyl)-5-aryl-N-substituted-4,5-dihydro-1H-pyrazole-1-carbothioamide derivatives were synthesized and evaluated in vitro for their monoamine oxidase (MAO) A and B inhibitory activity and selectivity. The derivatives substituted by halogen on the fifth position of pyrazole ring, inhibited MAO-A enzyme with a high selectivity index. On the other hand, compounds substituted with 2-naphthyl inhibited MAO-B enzyme with a moderate selectivity index. Docking studies were done to highlight the interactions of the most active derivative with the active site of MAO-A. In addition, in vivo antidepressant and anxiolytic activities of the compounds having selective MAO-A inhibitory effects, were investigated by using Porsolt forced swimming and elevated plus-maze tests respectively. 3-(4-Fluorophenyl)-5-(4-chlorophenyl)-N-allyl-4,5-dihydro-1H-pyrazole-1-carbothioamide has antidepressant, 3-(4-fluorophenyl)-5-(4-chlorophenyl)-N-methyl-4,5-dihydro-1H-pyrazole-1-carbothioamide and 3-(4-fluorophenyl)-5-(4-bromophenyl)-N-ethyl-4,5-dihydro-1H-pyrazole-1-carbothioamide have anxiolytic activity.
Keywords: 2-pyrazoline; 4,5-dihydropyrazole; monoamine oxidase; antidepressant; docking